Work Management in Improving the Quality of Nursing for Tuberculosis Patients - Septiani, Febi (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Primary health services are efforts made to increase access to quality health services. The increasing burden of tuberculosis in the world is inadequate health services, practices carried out that do not comply with SOPs, causing the detection of tuberculosis to worsen. Quality nursery provides services to achieve the patient's desires orexpectation. Service quality is influenced by Tangibles, Reliability, Responsiveness, Assurance and Empathy. Improving the quality of nursing in hospitals can be done with work management. Psychologically, they consider their work to be meaningful, there is a sense of responsibility for the work they do so that the results of their work can increase patient satisfaction. Performance management is a process used for planning, organizing, implementing, monitoring and evaluating. The aim of this research is to identify work management in improving the quality of tuberculosis nursing. The method used in this research is a literature review. The library sources used are laws and journals. Article literature sources consist of Scopus, Science direct, Proques, JSTOR, EBSCOhost, Spingerlink, Pubmed, Google Scholar. By using the keywords "tuberculosis", "patient perspective", "quality of nursing" and "performance". Work management requires planning, organizing, implementing, monitoring and evaluating to improve service quality. Facilities, good communication, ability to provide services, ability to help, listen and resolve patient complaints, provide attention and motivation can improve the quality of nursing. Work management in hospitals is very necessary to improve the quality of nursing services in hospitals Keywords:Tuberculosis, Patient Perspective, Nursing Quality, Work Management